WINDFALL PROFITS TAXES IN THE ENERGY CRISIS: DESIGN TRADE-OFFS, LEGAL CONSTRAINTS, AND INVESTMENT RISK - Rahman Putra; Retno Kusumastuti; Prianto Budi Saptono (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2026)
Energy price spikes in 2021–2022, intensified by Russia’s full-scale invasion of Ukraine, produced extraordinary upstream oil and gas earnings and, in several power markets, unusually high margins for inframarginal generators. Governments treated much of this upside as scarcity rent and moved quickly toward windfall profit taxes and revenue caps to finance household support while trying to preserve price signals. This integrative review synthesizes peer-reviewed evidence and authoritative institutional reporting on windfall taxation and related excess-profit instruments adopted from 2022 to 2025. The analysis centers on the European Union’s temporary solidarity contribution and inframarginal revenue cap, alongside the United Kingdom’s Energy Profits Levy, and uses these cases to connect rent-tax theory, empirical valuation effects, legal constraints, and administrative feasibility. The literature highlights a sharp trade-off. In principle, a levy confined to pure rents can raise substantial revenue with limited efficiency costs. Implementation usually relies on taxable-profit proxies, where measurement error, retroactivity narratives, and uneven national execution affect credibility and reshape investment risk. Event-study evidence reports material market revaluations around announcement dates, consistent with lower expected cash flows and a higher policy-uncertainty discount rate. Simulation studies suggest that financing targeted energy relief with windfall capture can outperform debt-only financing under plausible welfare weights, but outcomes remain sensitive to baseline selection, base definitions, and allowances that change marginal incentives. Treaty claims, constitutional challenges, and administrative constraints further condition results. The review concludes by distilling design principles for time-consistent rent capture that protect fiscal capacity without undermining long-horizon capital formation for the energy transition.